2021
DOI: 10.11648/j.plant.20210904.15
|View full text |Cite
|
Sign up to set email alerts
|

Correlation and Path Coefficient Analysis for Seed Yield and Yield Related Traits in Soybean (<i>Glycine max</i> (L.)) Genotypes

Abstract: Soybean is a very interesting food crops and several production constraints are accountable for the low productivity including poor soils fertility, lack of early maturing or drought tolerant variety, lack of high yielding varieties, disease and pest. Therefore experiment was conducted to assess the extent of genetic variability and traits associations in soybean genotypes for grain yield and its related components and thereby generate information as well as identify superior genotypes for further improvement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Highly positive genotypic correlations (P≤0.01) were identified for grain yield with plant height, number of pods per plant, number of primary branches per plant, hundred seeds weight, and harvest index. Similar results were reported by (Berhanu et al, 2021;Mili et al, 2017;Koraddi et al, 2015). The possible reasons for such a genotypic correlation may result from a pleiotropic effect or linkage of a gene governing the inheritance of these characters.…”
Section: Association Among Yield and Yieldrelated Traitssupporting
confidence: 87%
“…Highly positive genotypic correlations (P≤0.01) were identified for grain yield with plant height, number of pods per plant, number of primary branches per plant, hundred seeds weight, and harvest index. Similar results were reported by (Berhanu et al, 2021;Mili et al, 2017;Koraddi et al, 2015). The possible reasons for such a genotypic correlation may result from a pleiotropic effect or linkage of a gene governing the inheritance of these characters.…”
Section: Association Among Yield and Yieldrelated Traitssupporting
confidence: 87%
“…Karyawati and Puspitaningrum (2021) stated that seed yield is only directly correlated with the 100-seed weight and indirectly correlated with the number of pods filled and the number of seeds per plant. Berhanu et al (2021) reported that seed yield significantly correlated with the number of branches, nodes, seeds, and filled pods. Faot et al (2019) reported a correlation between disease scores, plant height, number of reproductive nodes, unfilled pods, seed size, and seed yield.…”
Section: Resultsmentioning
confidence: 99%
“…Seed yield ranged from 3.05 to 70.84 grams, with an average of 27.55 (Figure 1H). Berhanu et al (2021) reported that an increase in plant agronomic characteristics affects the number of seeds per plant. Several yield components, such as the number of nodes and pods, also support increasing soybean yield (Ferrari et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Complex quantitative traits in soybeans are usually interrelated (Berhanu et al, 2021) and influenced by both genetic and environmental factors (Wang et al, 2019). The QTL mapping efficiency and accuracy of quantitative traits could be largely influenced by the application in a single environment.…”
Section: Combination Of Different Methods Increased the Reliability O...mentioning
confidence: 99%